Exploring the predictors and prognostic significance of exercise-induced cardiac troponin release in master athletes following a 28 km mountain race. The Vamvakou research project. (23rd June 2022) - Stavroulakis, George; Methenitis, Spyridon; Koutroulis, George; Xanthis, Dimitrios; Cherouveim, Eugenia; Kroupis, Christos; Anastasiadis, George; Ketselidi, Kleopatra; Vlachopoulou, Elpiniki; Tsolakis, Charilaos; Koulouvaris, Panagiotis
ABSTRACT: Background/objective: Aetiology and significance of exercise-induced troponin release remains a contentious issue. We investigated the effect of a 28 km mountain run on cardiac troponin I (cTnI), in relation to training, performance, nutritional, biochemical and echocardiography variables, in a group of 25 recreational male master athletes. Material and methods: A comprehensive list of variables related with nutrition, training, performance and echocardiography, was collected pre- and post-race. Twenty-four months later, outcomes regarding cardiovascular events were obtained. Results: Serum cTnI values were increased after the race, with mean values rising from 7.2 ± 2.2 (before) to 80.0 ± 33.2 ng/L (post race), ( p < 0.001) and 23/25(92%) exceeding Upper Reference limit (50 ng/L). Echocardiography did not reveal significant alterations, or correlations with cTnI values. The percentage difference in hs-cTnI concentrations pre- and post-race correlated positively with age, race-induced changes of selected muscle damage indices, resistance training volume and negatively with endurance capacity and training volume (r: −0.727 to 0.725, p < 0.05). All athletes reported no cardiovascular event during the 24-month period post-race. Conclusion: cTnI elevation induced by a 28 km mountain running race was not correlated with echocardiographic, nutritional parameters and was less pronounced in athletes with larger endurance training history, in contrast with resistance training and age.